Kajian Peran Pemerintah dan Masyarakat dalam Menghadapi Alih Fungsi Lahan di Kelurahan Ciumbuleuit - Muhammad Yusuf Fauzan; Ernady Syaodih; Saraswati (Bandung Conference Series: Urban & Regional Planning, 2022)
Abstract. The development of urban areas is a phenomenon that occurs due to the rapid development of the population and human mobility. Sustainable Development Goals (SDGs) are a long-term world program to optimize all the potential and resources owned by each country. Land conversion is the change in the function of part or all of the land area from its original function to another function. As happened in Ciumbuleuit Village, there is a lot of agricultural land and even conservation land that has changed its land function to become a residential area. this is the reason behind the author conducting a study on the role of the government and society in dealing with land conversion. This study aims to see the impacts that occur due to land conversion and how much role the government and the community play in suppressing land conversion. The method used is descriptive qualitative with the MACTOR analysis method. Based on the results of the MACTOR analysis, actors who play an important role in handling land function change in Ciumbuleuit Village are the Bandung City Bappelitbang with a value of 39.8, the Bandung City National Land Agency with a value of 32.1 and the Bandung City Copyright, Construction Development, and Spatial Planning Office with a value of 20.4. Meanwhile, the main objectives that have the highest approval value are Increasing Public Awareness with a value of 23.2, Increasing Socialization of Spatial Allocation with a value of 21.2 and Suppressing RTH Land Conversion with a value of 20.7. Abstrak. Perkembangan wilayah kota merupakan satu fenomena yang terjadi karena pesatnya perkembangan penduduk dan mobilitas manusia. Sustainable Development Goals (SDGs) merupakan suatu program dunia jangka panjang untuk mengoptimalkan semua potensi dan sumber daya yang dimiliki oleh tiap negara. Alih fungsi lahan adalah perubahan fungsi sebagian atau seluruh kawasan lahan dari fungsinya semula menjadi fungsi lain. Seperti yang terjadi di Kelurahan Ciumbuleuit banyak sekali lahan pertanian bahkan lahan konservasi yang beralih fungsi lahan menjadi Kawasan permukiman. hal inilah yang melatarbelakangi penulis melakukan kajian mengenai peran pemerintah dan masyarakat dalam menghadapi alih fungsi lahan. Studi ini bertujuan untuk melihat dampak yang terjadi akibat alih fungsi lahan dan seberapa besar peran pemerintah dan masyarakat dalam menekan adanya alih fungsi lahan. Metode yang digunakan adalah deskriptif kualitatif dengan metode analisis MACTOR. Berdasarkan hasil analisis MACTOR aktor yang berperan penting dalam menangani alih fungsi lahan di Kelurahan Ciumbuleuit adalah Bappelitbang Kota Bandung dengan nilai 39.8 , Badan Pertanahan Nasional Kota Bandung dengan nilai 32.1 dan Dinas Cipta Karya, Bina Kontruksi, dan Tata Ruang Kota Bandung dengan nilai 20.4. Sedangkan tujuan utama yang memiliki nilai ketersetujuan tertinggi adalah Peningkatan Kesadaran Masyaraka dengan nilai 23.2, Peningkatan Sosialisasi Peruntukkan Ruang dengan nilai 21.2 dan Menekan Alih Fungsi Lahan RTH dengan nilai 20.7.